2015
DOI: 10.1136/vr.103034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the usefulness at national level of the dairy cattle health and production recording systems in Great Britain

Abstract: 17The aim of this study was to formally evaluate, qualitatively, the ability of existing recording

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…With this in mind, the present study was designed to provide prevalence estimates representative of the national GB dairy herd for several nonstatutory infectious diseases assumed endemic. Bovine tuberculosis, although identified as important during the workshop, was not included in the study due to the fact that existing mandatory surveillance provides reliable information on its occurrence at the national level (Velasova et al, 2015). Participation in the study was voluntary; however, when compared nationally, although the estimated weighted average herd size of 187 cows was slightly higher than that of 144 cows for the GB dairy herd, the estimated average annual milk yield was comparable with the national estimate of 7,535 L (DairyCo, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…With this in mind, the present study was designed to provide prevalence estimates representative of the national GB dairy herd for several nonstatutory infectious diseases assumed endemic. Bovine tuberculosis, although identified as important during the workshop, was not included in the study due to the fact that existing mandatory surveillance provides reliable information on its occurrence at the national level (Velasova et al, 2015). Participation in the study was voluntary; however, when compared nationally, although the estimated weighted average herd size of 187 cows was slightly higher than that of 144 cows for the GB dairy herd, the estimated average annual milk yield was comparable with the national estimate of 7,535 L (DairyCo, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of specific pathogens was based on the results of a workshop run by the Royal Veterinary College in April 2012. In the workshop, the participants were asked to identify and rank cattle health conditions considered important for individual farmers and the dairy industry for which no reliable and up-to-date nationwide estimates were available (Velasova et al, 2015). Additionally, 5 more pathogens for which no upto-date nationwide estimates were identified that could be detected using bulk milk samples and were included.…”
Section: Study Population and Sampling Designmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to recognise that timeliness should not be treated as the be all and end all of SyS. A fully electronic system built around a centralised database is still of limited value if the system is not reliable (functioning without fail) or accurate (complete and correct) [98] (see point 2 above). Finally, point 3 is not trivial given that the understanding of the relationships between different data streams can be poor when data are sparse and the events under consideration (such as disease outbreaks) occur infrequently.…”
Section: Discussionmentioning
confidence: 99%